Pursuit of liberation : critical service-learning as capacity building for historicized, humanizing, and embodied action - Nemeth, Emily Annette; Patterson, Ashley (Advances in service-learning research., 2022)
"The authors of this volume collectively demonstrate the importance of critical service-learning in this historic moment as we participate in, and witness ongoing struggles for justice around the world. The contributors of this volume offer guidance to educators and scholars alike who are interested in designing, participating in, and studying the potential of alliances formed through critical service-learning. The volume emphasizes theoretical and historical foundations of critical service-learning, pressing questions facing the field, exploration of outcomes of, and ongoing challenges for the pedagogy, and design features and larger scale models of critical service-learning that can be implemented across the educational landscape of elementary, secondary, and higher education"--